XIVth South-American Congress f Sports Medicine (Fiep Bulletin - online, 2015)
Being organized by the Argentinian Confederation of Athletics, this Congress was held in Buenos Ayres from 7th to 10th October 1967, during the XXIVth South American Athletics Championchip for men and the XIVth Championship for women.